Antioxidant and Antityrosinase Activities of Ethanolic Pachyrhizuserosus Peel and Tuber Extract (Majalah Kedokteran Bandung, 2019)
Aging process is a physiological process in living organisms caused by, among others, free radicals. One of the free-radical-related aging problems is skin hyperpigmentation (excessive melanin) due to increasing tyrosinase enzyme activities. Natural compounds are widely used as antioxidant and antiaging agents. Bengkuang (Pachyrhizuserosus) is known as a source of various active compounds which can be used against free radicals to reduce the risk of skin aging  through  tyrosinase enzyme inhibition. This study was performed in September 2018 in Aretha Medika Utama, Biomolecular and Biomedical Research Center, Bandung, Indonesia to examine the antioxidant and antityrosinase properties of Pachyrhizuserosus peel extract (PPE) and Pachyrhizuserosus  tuber extract (PTE).The extraction of PPE and PTE was performed using 70% ethanol by maceration method, followed by  phytochemical analysis using modified Farnsworth method. Antioxidant activities were measured through 2,2-Diphenyl-1-picrylhydrazil (DPPH) scavenging activities while antiaging assay were conducted through the  tyrosinase activity inhibition. In this study, PPE contained saponin, tannin, triterpenoid, and terpenoid while the PTE showed the presence of flavonoid, saponin, phenol, tannin, and alkaloid in phytochemical analysis. In the antioxidant assay, PPE presented a higher DPPH scavenging activities (IC50= 84.09 µg/mL) when compared to PTE (IC50= 98.30 µg/mL)(p
Keywords: Aging; antioxidant; hyperpigmentation; Pachyrhizuserosus; tyrosinase